(untitled) (TRAKIA JOURNAL OF SCIENCES, 2025)
Purpose: The emergence of the SARS-CoV-2 coronavirus has posed untold challenges to medical systems, as pregnant women are more susceptible to its harmful effects. Material/Methods: Clinical studies are seeking to understand the intricacies of the virus’s action during pregnancy, and to clarify the relationship between gestational infection with SARS-CoV-2 and mode of delivery. This literature review aims to explore and outline the existing knowledge related to different components of the topic, highlighting important subtopics such as: preterm birth, cesarean section, preeclampsia, preterm labor, and fetal distress. Results: Recent studies have shown a higher rate of preterm birth among pregnant women with SARS-CoV-2; and also that vaginal delivery is relatively safe with respect to SARS-CoV-2 infection in uncomplicated cases, but in complicated cases, cesarean section is a safe method. In addition to the complexity, gestational infection and SARS-CoV-2 infection can be followed by complications such as preeclampsia and premature rupture of membranes, additional factors determining the mode of delivery. Conclusions: In this context, the aim of this literature review is to critically analyze the available information on the association between gestational infection with SARS-CoV-2 and the mode of delivery, shedding light on key issues related to clinical care and guiding future research efforts.